2016
DOI: 10.1007/s10653-016-9844-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PM2.5, CO2 and particle-number concentration in mass transit railway carriages in Hong Kong

Abstract: Fine particulate matter (PM) levels, carbon dioxide (CO) levels and particle-number concentrations (PNC) were monitored in train carriages on seven routes of the mass transit railway in Hong Kong between March and May 2014, using real-time monitoring instruments. The 8-h average PM levels in carriages on the seven routes ranged from 24.1 to 49.8 µg/m, higher than levels in Finland and similar to those in New York, and in most cases exceeding the standard set by the World Health Organisation (25 µg/m). The CO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Nowadays, field measurement campaigns are commonly deployed for micro-environmental characterization of urban subway systems [16,53,65]. Data obtained in these campaigns could then serve for the evaluation or internal correlations of sub-MEs [42,66]. The findings of this research therefore make them possible to be the foundation of sub-ME-related standards or norms in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, field measurement campaigns are commonly deployed for micro-environmental characterization of urban subway systems [16,53,65]. Data obtained in these campaigns could then serve for the evaluation or internal correlations of sub-MEs [42,66]. The findings of this research therefore make them possible to be the foundation of sub-ME-related standards or norms in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vânia Martins et al demonstrated that ventilation and air conditioning systems could improve subway air quality [11]. Non-ambient sources are main significant contributors to total metro PM exposure [31,42], including emissions from rail mechanical abrasion, and dust particle resuspensions from passenger activities [5,43]. It is therefore recommended to adopt some air protective solutions in station halls or platforms, such as utilizing air sterilization apparatus, strengthening dustproof function through grid design, installing platform screen doors (PSD), and reducing combustion sources as much as possible [35].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted inside Hong Kong buses has shown that high CO 2 averages of 3692 ppm and brief peaks such as 5773 ppm are possible. Other similar studies inside public transportation have reported lower averages with ranges from 714 to 1801 ppm [3]. These values do not present serious health risks, as they do not come close to the short term exposure limit (STEL) of 30,000 ppm established by the U.S. Occupational Safety and Health Administration (OSHA).…”
Section: Introductionmentioning
confidence: 64%
“…This was expected, as the school period is often associated with busier public and private transportation. CO 2 concentrations inside the metro platform and metro carriage presented lower concentrations than the Shanghai metro system carriages [3]. We averaged the median values for both periods, giving us a concentration of 757.5 ± 135.5 ppm, while the Shanghai metro carriages had mean values of 1253.1 ± 449.1 ppm [35].…”
Section: Discussionmentioning
confidence: 99%
“…particles) to minimize exposure risks to occupants. 69 Indoor CO 2 can be considered as a good indicator of IAQ, 1012 especially in the high-density buildings, 1318 where the CO 2 emitted by occupants can be seen as the main indoor pollutant. For instance, IAQ is considered acceptable by maintaining a steady-state CO 2 concentration no greater than 700 ppm above outdoor air level in a living space, based on the ASHRAE 62–2013 Ventilation Standard.…”
Section: Introductionmentioning
confidence: 99%